A study on residential location of information, communication and technology (ICT) sector employees working in Kuala Lumpur city - Mohit, Mohammad Abdul (s.n, 2013)
Employment and residential location are interconnected in urban areas. To understand the internal dynamics between location of employment and housing, it is important to identify and analyze the various factors and the extent to which these factors influence the residential location choice. The identified factors are important to determine the future physical form of the cities, transport policies and other development policies. This report attempts to study and analyze the residential location of Information Technology and Communication (ICT) sector employees in Kuala Lumpur city. This study explores a different dimension, which are currently lacking in the existing studies by narrowing the subject to only ICT sector employees in Kuala Lumpur. Finally, the study intends to provide an essential understanding of residential location of ICT sector employees in Kuala Lumpur and a substantial step for further empirical research. Finding from this study is expected to assist in land use planning, housing and infrastructure policies formulation and also to provide a general idea of future housing demand for the private developer and other relevant agencies